Penanganan Problem Remaja Melalui Pendekatan Psikologis (Analisis Kasus Remaja Broken Home) - Andriani Andriani (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2022)
The purpose of this paper is to explain the form of handling adolescent problems through an approach to (analysis of cases of broken home adolescents). The method used is descriptive qualitative which is to analyze the phenomena that have occurred in broken home families. Every married couple hopes that their marriage relationship will last until the end of life. However, it is the opposite of what is dreamed of, which is to become a family that has a rift in it and the family atmosphere is no longer harmonious, causing a huge impact on both married couples and teenagers. This is what makes teenagers experience problems as a result of broken homes /cracks in the family, namely teenagers are concerned about the environment, feel depressed, more easily angry, and always feel sad. As well as the efforts made by parents by taking a persuasive approach to adolescents, providing coaching/providing advice, providing the best solutions in order to make people who are beneficial to themselves and the surrounding environment.